1981
DOI: 10.1177/00220345810600051701
|View full text |Cite
|
Sign up to set email alerts
|

Pulpal Reaction to Bleaching of Teeth in Dogs

Abstract: Hydrogen peroxide and heat are two components of a technique commonly used to bleach human teeth. The effects of these two components on pulp tissue of dog teeth were evaluated histologically. Hydrogen peroxide alone or with heat caused obliteration of odontoblasts, hemorrhage, resorption, and inflammatory infiltration, while heat alone was not detrimental. Pulpal changes demonstrated evidence of reversibility after 60 d.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
79
0
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 9 publications
4
79
0
5
Order By: Relevance
“…1,6 The present study also showed a cytotoxic effect of the substances released by the bleaching gel, that was transient once the laser irradiation was able to offset this effect. In fact, different levels of cellular response to substances released by the bleaching agent were observed.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…1,6 The present study also showed a cytotoxic effect of the substances released by the bleaching gel, that was transient once the laser irradiation was able to offset this effect. In fact, different levels of cellular response to substances released by the bleaching agent were observed.…”
Section: Discussionsupporting
confidence: 60%
“…[2][3][4] When it reaches the pulp chamber, it can trigger reversible inflammation. 5,6 Tooth bleaching agents, carbamide peroxide or hydrogen peroxide, undergo ionization and decay, producing free radicals. Free radicals are highly unstable and exhibit remarkable ability to react with other organic substances 7 and may even cause damage to cellular DNA.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is known that the aggressiveness of a bleaching gel depends not only on its application time on enamel (10), but also on the H 2 O 2 concentration in the product. The increase of the bleaching time may result in a deeper penetration of the components released from the bleaching gel, which may cause severe damage to the pulp tissue (10,18). The penetration of H 2 O 2 -based bleaching agents into the dental structure causes different alterations in vital teeth (3) and some products resulting from H 2 O 2 degradation, such as OH -and other ROS, may cause lipid peroxidation and protein fragmentation with consequent cell membrane damage (9).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that the application of a 33% H 2 O 2 bleaching gel for 30 min on the enamel of canine teeth was capable to produce damage to odontoblast-like cells and internal inflammatory root resorption (10). In the present study, in addition to us- ing teeth with structural characteristics and hard tissue thickness similar to those of human teeth, a long total bleaching time was established (75 min, distributed in five 15-min consecutive applications) in order to simulate a frequent clinical situation in vital tooth bleaching therapies to whiten severely darkened teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Carrasco ve arkadaşları 12 yaptığı çalışma sonucunda kullandıkları diyot Lazer, plazma ark lambası, kuartz tungsten halojen ışık kaynaklarının LED' e kıyasla yüksek pulpa odası sıcaklık artışlarına neden olduğunu bildirmişlerdir. Sarı ve arkadaşları 13 16 Rhesus maymunlarında yaptıkları çalışmalarda; 2, 14, 56 ve 93 günlük periyotlar sonunda bilinen yüzeysel ısı artışlarını histolojik olarak gözlemlenebilir pulpal hasarlarla alakalandırmışlar ve bu amaçla pulpa duvarında istenilen sıcaklığa ulaşana kadar sağlıklı bir dişin bukkal yüzeyine 275 ° C ' lik lehim uygulamışlardır. Bu çalışmanın sonuçlarına göre 5.5 °C ısıtılan dişlerin %15' inin ve 11.1 °C ısıtılan dişlerin % 60' ının irreversibl hasar aldığını bildirmişlerdir.…”
Section: Introductionunclassified